THE STUDENTS’ AND TEACHERS’ PERCEPTION OF ENGLISH TEACHER PERFORMANCE AT SMA BRIGJEND KATAMSO 2 - Fara Fadhila; Ali Wafa (Merwin Publisher, 2025)
Perception is the process by which individuals interpret and understand their surroundings based on their experiences, knowledge, and expectations. Students' perception of their teachers is shaped by various factors, including teaching methods, classroom management, attitude, and engagement. These perceptions significantly impact students' motivation, learning experiences, and overall academic performance. In the context of education, students' perception of their teachers plays a significant role in determining their learning experience and academic performance. This study was carried out to determine how students perception on English teachers This study was carried out to determine students' perceptions of English teachers. The research design of this study is qualitative, where data were collected from three English teachers and forty students from classes X, XI, and XII at SMA Brigjend Katamso 2. The researchers conducted interviews and distributed questionnaires to each respondent to gather insights into their views on English teachers' teaching effectiveness and classroom management. In this situation, the teacher must be aware of the approach taken in the learning process, and the students must be able to determine how well the teacher is performing. As a result, English teachers can implement various learning models, classroom management, student motivation, facility use, and positive student experiences; their performance in teaching English is good, according to this study. Additionally, for educational this approach involves the teacher using a learning model that is more in line with the content being taught to the students rather than a unique method. But for the learning process to be successful, educators will innovate and enhance their teaching strategies.